DECONSTRUCTING PARADISE: WE NARRATION AS COLLECTIVE INDIGENOUS VOICE IN “THIS IS PARADISE” - Kristiawan Indriyanto (International Journal of Humanity Studies (IJHS), 2022)
This paper contextualizes how a short story “This is Paradise” by Kristiana Kahakauwila deconstructs the idealized trope of Hawai’i as paradise by presenting a localized narration from the perspective of the indigene working within the tourist industry. The use of first-person plural narration as the focalizer echoes the collective voice of the Hawai’ian indigene in their marginalized status within the tourist industry. An econarratological perspective as stated by Erin James provides reader with textual cues necessary to construct a mental model of Hawai’i from the insiders’ perspective. Kahakauwila’s use of insiders’ perspective enables reader to have an understanding of indigenous marginalization in Hawai’i, informed by a local experience of place. This perspective challenges the common depiction of Hawai’i as seen from the outsider/tourist point of view. The present study concludes how “This is Paradise” underlines a localized portrayal of the Hawai’i as the counter narrative toward the established trope of Hawai’i as paradise through its use of first-person plural and spatialization of Waikiki.